Vom Dramma per musica zur kirchenmusikalischen Praxis – Geistliche lateinische Kontrafakturen italienischer Opernarien in mährischen Klöstern und Kirchen - Undine Wagner (Musicologica Brunensia, 2014)
Until the Josephine reforms and to a limited extent even after them – in addition to the music ensembles supported by aristocracy – the churches, monasteries and church foundations were the most important centers of cultivation of music in the Czech lands. In the hands of religious convents was the entire higher music education, the foundations for the preserving of choral music played a significant role. Through close ties of the orders to Italy, but also to cities such as Dresden or Vienna, Italian music spread rapidly into the Czech lands. The rich and often challenging repertoire of church music included also numerous Latin spiritual contrafacta whose originals came from Italian operas. -- A complete overview of the traditional spiritual Latin contrafacta from Italian operas and occasionally from oratorios transferred to Moravia and Moravian Silesia can not presently be provided. The present results of the first inventory of yet provable contrafacta are based on a preliminary, incomplete and rather random selection, enabled by the research carried out on the basis of the RISM database. Thus, only those music collections could be considered their music manuscripts are included completely with music incipits in the RISM. In the RISM bibliographic records many contrafacta are already declared as such. Thanks to the music incipits search were further Latin pieces – partly provided with composer names, partly anonymous – identified as contrafacta with determination of their Italian originals. In addition to a rather narrow evaluation in the text the exploratory results were tabulated – in Table 1 are listed the spiritual contrafacta and their originals sorted by composers and works, in Table 2 listed alphabetically according to the Latin text incipits. Table 3 provides information on concordances to the Moravian contrafacta detectable in collections both within and outside of the Czech lands.